Plasmodium falciparum Multidrug Resistance Proteins (pfMRPs) - Gil, José Pedro; Fançony, Cláudia (Frontiers in Pharmacology, 2021)
The capacity of the lethal Plasmodium falciparum parasite to develop resistance against anti-malarial drugs represents a central challenge in the global control and elimination of malaria. Historically, the action of drug transporters have been known to play a pivotal role in the capacity of the parasite to evade drug action. MRPs (Multidrug Resistance Protein) are known in many phylogenetically diverse groups to be related to drug resistance by being able to handle a large range of substrates, including important endogenous substances as glutathione and its conjugates. P. falciparum MRPs are associated with in vivo and in vitro altered drug response, and might be important factors for the development of multi-drug resistance phenotypes, a latent possibility in the present, and future, combination therapy environment. Information on P. falciparum MRPs is scattered in the literature, with no specialized review available. We herein address this issue by reviewing the present state of knowledge.